A new method for voice signal features creation - Majed O. Al-Dwairi; Amjad Y. Hendi; Mohamed S. Soliman; Ziad A. A. AlQadi (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Digital audio is one of the most important types of data at present. It is used in several applications, such as human knowledge and many security and banking applications. A digital voice signal is usually of a large size where the acoustic signal consists of a set of values distributed in one column (one channel) (mono signal) or distributed in two columns (two channels) (stereo signal), these values usually are the results of sampling and quantization of the original analogue voice signal. In this paper we will introduce a method which can be used to create a signature or key, which can be used later to identify or recognize the wave file. The proposed method will be implemented and tested to show the accuracy and flexibility of this method.